“Indahnya Pelangi di Piring Makanku” Edukasi Gizi Stunting Pada Guru PAUD, Ibu PKK, dan Kader di Kelurahan Bukit Betung Kabupaten Bangka - Ratmawati Ratmawati; Ori Pertami Enardi; Emmy Kardinasari; Karina Dwi Handini (LPPM UNINUS, 2021)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition. Stunting affects brain growth and development and increases the risk of developing chronic diseases as adults. Knowledge, attitudes and behaviour are factors that can affect nutritional status. Insufficient knowledge about nutrition affects the ability to apply and practice the nutritional principle in life. Various efforts have been applied to increase knowledge through nutrition education. The “Isi Piringku” concept consists of education on the importance of balanced nutritional intake according to the children’s respective needs in age 4–6 years. Educating the community through promoting“Isi Piringku” in a fun concept of a rainbow in one plate conducted at Bukit Betung Village aimed to overcome stunting. The purpose of the activity was to increase knowledge and induce a change of attitudes in PAUD (Pendidikan Anak Usia Dini/Early Childhood Education) teachers, PKK (Pemberdayaan Kesejahteraan Keluarga/Family Wellbeing Empowerment) members, and cadres in applying the concept of “beautiful rainbow on my plate”. The educational method was counselling with booklets and a contest on “the beauty of a rainbow on my plate”. The activity was held at the Bangka Regency Women's Building for two days, namely nutrition education on the first day and a contest of “beautiful rainbow on my dinner plate” on the second day. The target of activities for PAUD teachers, PKK members, and cadres was a total of 55 people. The analysis of the results of the pretest and posttest becomes a benchmark for knowing an increase in knowledge. Changes in participant attitudes were observed based on the results of competition assessments with evaluation criteria as follow: taste, variations in processing, appearance, presentation, serving accuracy, and cleanliness. The results of the activity showed that the participants were mostly mothers (96.4%) with an average age of 41 years and 61.8% had received information about the “Isi Piringku”. There was an increase in participants' knowledge from 86.3% to 92.7% in the “good” category. The target of the activity was achieved by observing an increase in knowledge 80% and a change in the attitudes of PAUD teachers, PKK members, and cadres in providing balanced nutritious food based on the concept of the “Isi Piringku”.